Effect of Vitamin K2 as A Stimulants of Bone Regeneration in Osteoporosis Therapy - Bohlouli, Mahboubeh; Nokhbatolfoghahaei, Hanieh; Rasouli-Ghahroudi, Amir Alireza; Khojasteh, Arash (Regeneration, Reconstruction & Restoration (Triple R), 2020)
Introduction: Osteoporosis stems from misbalance between bone forming and bone resorption, which lead to increased risks of bone fractures. In recent years, stem cell therapy introduced as a promising strategy for bone regeneration in osteoporosis due to their bone regeneration potential. However, stem cells require different stimulator to accelerate bone regeneration and repair processes. Previous Studies showed that Vitamin K2, as an osteoprotective factor, promote and inhibit proliferation and activity osteoblast and osteoclasts cell line, respectively. We aimed to elucidate effect vitamin K2 on dental pulp stem cells (DPSCs) proliferation and their differentiation into osteoblast, and evaluation effect of this vitamin on the process of differentiating peripheral blood mononuclear cells (PBMNCs) into osteoclast and the activity of these cells. Material and Methods: DPSCs and PBMNCs were used for induction towards the osteoblast and osteoclasts, respectively in the presence of various concentrations of vitamin K2. Cell viability was assessed by MTT assay. Osteogenesis assayed by alizarin red S staining and osteogenic gene expression as well as osteoclastogenesis by tartrate-resistant acid phosphatase (TRAP) staining, Annexin V/PI assay, pit formation and NF-κB gene expression. Results: Our data showed that vitamin K2 at a concentration of 10µM increased both proliferation and osteogenesis activities of DPSCs and also increased the incidence of apoptosis in TRAP-positive cells as well as decrees in an expression of NF-κB and pit formation. Conclusion: These results suggest that simultaneous use of vitamin K2 and DPSCs can be a purpose of stem cell therapy in osteoporosis and conducting further pre-clinical studies.